Treatment and pattern of bone metastases in 1094 patients with advanced breast cancer – Results from the prospective German Tumour Registry Breast Cancer cohort study. (July 2017) - Schröder, Jan; Fietz, Thomas; Köhler, Andreas; Petersen, Volker; Tesch, Hans; Spring, Lisa; Fleitz, Annette; Jänicke, Martina; Marschner, Norbert
Abstract: A high proportion of patients with breast cancer develop bone metastases, yet data on routine treatment with bone-targeted agents (BTA) are rare. We report real-life outcome data of patients with breast cancer metastasised to the bone treated by office-based oncologists in Germany. The ongoing, prospective, multicentre, population-based cohort study Tumour Registry Breast Cancer (TMK) was started in 2007 in 140 centres across Germany. This interim analysis of 1094 patients with bone metastases revealed differences among the tumour subtypes: at start of first-line therapy, 36% of the patients with hormone receptor (HR)-positive and only 20% of the patients with HR-negative tumours presented with bone-only metastasis. The majority of patients with bone metastases (89%, n = 976) received BTA therapy. In 2014–2015, 37% of the patients received the bisphosphonate zoledronic acid and 36% the antibody denosumab. Median duration of BTA therapy was 20 months (interquartile range 31.5 months), starting a median of 3 weeks after diagnosis of bone metastases, and ending a median of 7 weeks before death. The median overall survival (OS) also varied among the types of metastasis at start of first-line therapy ranging from 54 months (95% confidence interval [CI] 37.6–70.8), 38 months (95% CI 29.4–44.2) to 28 months (95% CI 24.2–31.0) for patients with bone-only metastases, non-visceral with or without bone metastases and visceral with or without bone metastases respectively. We show that choice and duration of BTA therapies are in conformity with guidelines applicable in Germany. To our knowledge, this is the first presentation of data on incidence, metastatic pattern, treatment and survival of patients with bone metastases in routine practice. Highlights: We present real-life data on 1094 patients with breast cancer and bone metastases. Of the above, 89% of the patients in routine care received bone-targeted agents (BTA). In 2014–2015, 36% of the patients received denosumab and 37% zoledronic acid. BTA therapy was started shortly after diagnosis; median duration was 20 months.